Profiles and behavioral consequences of child abuse among adolescent girls and boys from Barbados and Grenada. (May 2018) - Debowska, Agata; Boduszek, Daniel; Sherretts, Nicole; Willmott, Dominic; Jones, Adele D.
Abstract: The current study used latent class analysis to uncover groups of youths with specific abuse (physical, emotional, and sexual) profiles in and outside the family, and identify how membership in each abuse group is associated with behavioral outcomes. Data were collected among a sample of male ( n = 662; M age = 13.02 years) and female ( n = 689; M age = 12.95 years) children and adolescents (9–17 years old) from Barbados and Grenada. Self-report surveys were completed by participants in school settings. Three latent classes of child abuse were distinguished among boys, including 'low abuse' (39.2% of the sample), 'physical and emotional abuse high outside/medium in the family' (43.2%), and 'high overall abuse' (17.6%). Among girls, four unique classes were recovered: 'low abuse' (40.7%), 'high physical and emotional abuse outside the family' (7.6%), 'high emotional and moderate physical abuse' (33.9%), and 'high overall abuse' (17.8%). Compared with members of low abuse groups, youths who reported having experienced high/moderate levels of various forms of violence, including those who were abused in multiple ways and across the two settings ('high overall abuse'), were significantly more likely to engage in violent and hostile behavior. Abused and non-abused youths did not differ on non-violent conflict resolution skills. The significance of present findings for future research and practice is discussed.